The Impact of Stator Tooth and Pole Combinations on Output of a Dual Stator Electric Machine - Awah, C. C; Amaghionyeodiwe, C. A.; Diyoke, G. C.; Obasi, O.; Nnabuenyi, I. K.; Oti, S. E. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2025)
Abstact